1996
DOI: 10.1007/bf01712175
|View full text |Cite
|
Sign up to set email alerts
|

Albumin bolus administration versus continuous infusion in critically ill hypoalbuminemic pediatric patients

Abstract: The half-life of exogenous albumin in the critically ill hypoalbuminemic pediatric patient is short if given as a bolus. Continuous infusion therapy appears to be more efficacious in increasing BAC over time, as the half-life with this method appears to be longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…It remains unclear the reasons of the rapid decrease in plasma albumin concentration 48 h after administration since the reported life-time of monomeric albumin in humans is in the range of 28–36 days 38 . However, our finding is in line with that observed in analbuminemic patients and adult Gunn rats infused with HSA 33 39 40 , where plasma albumin levels increased immediately after infusion, but substantially decreased 24 h post-treatment. Moreover, it was shown that albumin half-life in mice infused with mouse albumin was 35 h 41 while that of mice infused with HSA was 21 h 42 .…”
Section: Discussionsupporting
confidence: 92%
“…It remains unclear the reasons of the rapid decrease in plasma albumin concentration 48 h after administration since the reported life-time of monomeric albumin in humans is in the range of 28–36 days 38 . However, our finding is in line with that observed in analbuminemic patients and adult Gunn rats infused with HSA 33 39 40 , where plasma albumin levels increased immediately after infusion, but substantially decreased 24 h post-treatment. Moreover, it was shown that albumin half-life in mice infused with mouse albumin was 35 h 41 while that of mice infused with HSA was 21 h 42 .…”
Section: Discussionsupporting
confidence: 92%
“…First, STB is a chronic wasting disease with 25.7% of patients experiencing pulmonary tuberculosis as a complication. These patients have high nutritional requirements and lower protein intake, and the inflammation caused by the tuberculosis infection increases albumin consumption, which in turn leads to the half-life time of albumin being decreased to 8.2 ± 1.4 days, while the normal value is 12.5 ± 1.7 days [ 22 , 23 ]. Second, debridement surgery in patients with STB is a critical factor that can lead to low postoperative albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in serum albumin to levels above 2 g/dL might be associated with less edema. Intradialytic albumin infusions enabled removal of excess fluids in the first 2 weeks, but probably did not contribute to the increase in serum albumin level, as it was shown that albumin infusion during several hours even in catabolic patients without proteinuria had no significant effect on serum albumin level after 24 hr ( 29). Though normal serum albumin levels are difficult to achieve, there was a significant elevation to the level of 2 g/dL within two weeks after initiation of therapy, which could help in moderating edema.…”
Section: Discussionmentioning
confidence: 99%